TINGKAT LITERASI MEDIA PADA MAHASISWA (Studi Deskriptif Pengukuran Tingkat Literasi Media Berbasis Individual Competence Framework Pada Mahasiswa Departemen Ilmu Komunikasi USU) - Rebekka Purba (FLOW, 2015)
The study is titled “Literacy Media Levels Based on Individual Competence Framework for Communication Science Student”. This research use the descriptive analyse, to describe the fact and character carefully. The aim of this researh is to see how the lieracy media levels on communication science USU student. Theory which is relevan with the research are mass communication and litercay media. All population in this research is 395 people and use 152 sample based on Surakhmat’s sample retraction formula. Retraction sample technic is using proportional stratitified sampling and random sampling that all population have the same oportunity as a sample. This research used a questioner that arranged by indicator based on individual comptence framework. Then, all information and data analysed by singular table used SPSS (Statistical Product Service Solution) 13.0. The result showed that the litercay media communication science USU student levels is medium levels. This result means that the individual knows how to obtain and evaluate the information required, he evaluates the information search strategies, but they must increase their abilityto analyse and evaluated the information. Literacy media educated is so crucial in this media-saturated era especially for communication science student to make them responsive to all information around them carefully. Keyword: Literacy Media, Individual Competence Framework, Mass Communication, Literacy Media Level